GOOD CORPORATE GOVERNANCE, KINERJA KEUANGAN, DAN PENGUNGKAPAN SUSTAINABILITY REPORT: STUDI PADA SUBSEKTOR PERBANKAN DI BEI 2019–2023 - Margareth Hasian Siagian; Astrini Aning Widoretno (Pusat P2M Politeknik Negeri Batam, 2025)
This study examines the effect of Good Corporate Governance and Financial Performance on the disclosure of sustainability reports in Indonesian banking companies. Even though POJK No. 51/POJK.03/2017 requires banks to implement sustainable finance, in practice the disclosure of environmental aspects is still far behind social and economic aspects. The purpose of this research is to test whether managerial ownership, independent commissioners, board of directors, and return on assets (ROA) influence the level of sustainability report disclosure. The study uses a quantitative method with secondary data from 15 banks listed on the Indonesia Stock Exchange during 2019–2023, giving 75 firm-year observations. Data were analyzed using multiple linear regression. The results show that all variables have a effect. Managerial ownership gives the strongest influence, followed by independent commissioners, ROA, and the board of directors. The model explains 78.8% of the variation in disclosure. This research supports Stakeholder Theory, showing that governance and financial performance strengthen accountability to stakeholders. In practice, the findings suggest that stronger governance quality and financial performance can encourage banks to be more transparent and accelerate sustainable finance in Indonesia.